The impact of FDI on child labor: Insights from an empirical analysis of sectoral FDI data and case studies - Doytch, Nadia (Archīum Ateneo, 2014)
Not all foreign direct investment (FDI) is alike as far as its impact on various dimensions of human development is concerned. This paper focuses, in particular, on child labor and it undertakes a cross-country empirical analysis of this issue, using data on 100 countries spanning the period 1990–2009. Unlike earlier studies that focus mostly on total FDI, we also utilize data on disaggregated FDI, covering the main economic sectors of interest such as agriculture, mining, manufacturing, services, and finance. The empirical results suggest that different economic sectors generate varied effects on child labor. For instance, FDI in agriculture in Europe and Central Asia tends to exacerbate child labor, whereas FDI in manufacturing in South and East Asia and FDI in mining in Latin America appear negatively linked to child labor. Furthermore, signing on to the UN Convention on the Rights of the Child (CRC) is positively associated with child labor. One possible explanation for the latter result is that stronger anti-child labor laws could lead to multiple equilibria in labor markets, including the possibility of increasing child labor in certain sectors. Selected case studies help clarify the possible reasons behind this varied FDI impact on child labor, emphasizing among other factors supply chain management and the critical importance of policy implementation and coordination with the private sector.